NASIB ANAK INDONESIA DI TENGAH KRISIS MORAL BANGSA - Sigit Astono (Gelar : Jurnal Seni Budaya, 2012)
This paper explores the deterioration of mental, moral and spiritual Indonesia swept this nation recently (2012). Like a disease, then the condition of Indonesia has become more acute and immediate treatment is needed and the right drug to cure the disease. Presumably this is because the orientation of people the wrong way in realizing the ideals of a just and prosperous as strong lately. The attitude of materialism, hedonism and spiritual arrogance crashing in almost all walks of life. Start of rural people to the power elite, all compete without feeling embarrassed, ashamed and willing degrading morals to get what they want. The process is bizarre and ridiculous thing to do, therefore, is not fighting over anything taboo thing to do. So greedy and fierce, until people forget that their ancestors have inherited a rich treasure inexhaustible to enjoy the arts and culture. Now is the time for awareness to be made by all components, ranging from the ordinary to the level of policy makers. The main source of this writing as a tool of analysis is the study of literature. In addition, supporting data was obtained through the print and electronic media sources and experience as participant observer. Key wordsÂ :Â art education, moral, multiple intelligence theory, and the Book Wulangreh